Gambaran Pengetahuan Dan Sikap Pembeli Terhadap Kandungan Klorin Pada Beras Yang Dijual Di Pasar Kranji Bekasi - Risda Lestari; Nur Asiah; Awaluddin Hidayat Ramli Inaku (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Chlorine is a chemical that is usually used as a germ killer. In addition, chlorine is also commonly used for clothing and paper, but an important concern is when chlorine is used as an ingredient in rice whitening, because the chlorinated rice will look like super-quality rice. The purpose of this study was to determine the buyer's knowledge and attitudes about the chlorine content of rice and to determine the chlorine content in the rice sold at Kranji Market in Bekasi. This research is a descriptive survey research. The objects in this study were 100 (One Hundred) respondents and 10 (ten) types of rice and were then examined at UPT Tangerang City Health Laboratory using the Uv-Vis Spectrophotometry Test. The sample technique is Accidental Sampling. The research instrument uses a questionnaire sheet. Univariate results show that 80% of rice buyers have low knowledge of rice containing chlorine and rice buyers have a positive attitude towards consumption of rice containing 63% of chlorine. Based on this research, it is suggested for buyers to be more careful in choosing the rice to buy as a form of prevention to maintain health from the dangers of using chlorine in rice when consumed.